2013
DOI: 10.1097/shk.0b013e3182894016
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmolarity Attenuates TNF-α–Mediated Proinflammatory Activation of Human Pulmonary Microvascular Endothelial Cells

Abstract: Firm neutrophil (PMN)-endothelial (EC) adhesion is crucial to the PMN-mediated hyperinflammation observed in acute lung injury. Hypertonic saline (HTS) used for resuscitation of hemorrhagic shock has been associated with a decreased incidence of PMN-mediated lung injury/acute respiratory distress syndrome. We hypothesize that physiologically accessible hypertonic incubation (170mM vs. 140mM, osmolarity ranging from 360-300 mOsm/L) inhibits pro-inflammatory activation of human pulmonary microvascular endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…[51][52][53][54] It leads to defective phagocytosis, and intracellular killing of bacteria. 51,[54][55][56] Thus, in a hyperosmolar milieu, the classical neutrophil-related innate defense mechanisms seem to be compromised. Viewed in this context, the release of NETs from neutrophils in response to hyperosmolarity would seem to offset the loss of classical neutrophil-related innate defense mechanisms such as phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52][53][54] It leads to defective phagocytosis, and intracellular killing of bacteria. 51,[54][55][56] Thus, in a hyperosmolar milieu, the classical neutrophil-related innate defense mechanisms seem to be compromised. Viewed in this context, the release of NETs from neutrophils in response to hyperosmolarity would seem to offset the loss of classical neutrophil-related innate defense mechanisms such as phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…We used these to determine whether the intracellular response to HOsm required ion flux to achieve anti-inflammatory benefit. We and others have used modest hyperosmolarity of about 400 mOsm against various cells [1] , [27] , [35] , [36] , [37] . These doses were derived from peak levels achievable in animal models and substantial cell shrinkage or death ( Fig 7 ) are not evident.…”
Section: Discussionmentioning
confidence: 99%
“…B, Likewise, the VEGF protein expression (red) in the GFAP-positive TNC1 astrocytes (green) was obviously increased at 24 h in the OGD group compared with that in the control group; however, its expression was decreased in the HS group compared with those in the corresponding groups. 33,34,[37][38][39][40] An animal experiment found that HS may ameliorate the brain edema and brain injury induced by traumatic brain injury by reducing TNF-ɑ-and IL-1β-mediated pro-inflammatory activation. 25,31 In this study, the in vitro and in vivo results show that HS can reduce the activation of the NLRP3 inflammasome and its adaptor protein apoptosis-associated speck-like protein (ASC) in microglia.…”
Section: F I G U R Ementioning
confidence: 99%
“…In this study, we found that 10% HS can reduce the release of IL-1β by inhibiting the activation of the NLRP3 inflammasome in microglia and then downregulates the astrocyte-derived VEGF expression by inhibiting the activity of the IL-1β/IL1R1/NF-кB signaling pathway in astrocytes in focal ischemic stroke in rats. As a result, HS alleviates It is well documented that HS has an antiinflammatory effect and exerts the function of organ protection induced by trauma-hemorrhagic shock,[32][33][34][35] acute pancreatitis, 36 traumatic brain injury,31 and ischemic stroke 25. Studies have shown that HS can…”
mentioning
confidence: 99%